Prestige of the legal professions in the representation of students - Мурзіна, Олена Анатоліївна (Науковий журнал L'Association 1901 «SEPIKE», 2014)
The article deals with the prestige of the legal profession among students of Zaporozhye Law Institute. Actuality of the affected theme and the ambiguity of interpretations of the concept of prestige necessitate further study of this important category. Prestige is a reflection in the public consciousness of the real situation in the system of social relations of the individual, social, professional groups and the like, which characterizes the influence and respect that they enjoy in society. In a more narrow sense, the prestige is a place, significant from the viewpoint of public opinion by a certain social status in the hierarchy of other statuses. To investigate the prestige of the legal profession the technique “Square of professions” has been used. Studies were conducted among students of I and IV courses of Zaporozhye Law Institute
Keywords: prestige; Square of professions; type of professions; human- technology